Comparison of organelle genomes between endangered mangrove plant Dolichandrone spathacea to terrestrial relative provides insights into its origin and adaptative evolution - Zhang, Ying; Zhang, Jingwen; Chen, Zewei; Huang, Yanni; Liu, Jiaxuan; Liu, Yuqi; Yang, Yong; Jin, Xiang; Yang, Yuchen; Chen, Yiqing (Frontiers in Plant Science, 2024)
Dolichandrone spathacea is a mangrove associate with high medicinal and ecological values. However, due to the dual-pressure of global climate change and human activities, D. spathacea has become endangered in China. Moreover, misidentification between D. spathacea and its terrestrial relatives D. cauda-felina poses further challenges to field protection and proper medicinal usage of D. spathacea.Thus, to address these problems, we sequenced and assembled mitochondrial (mt) and chloroplast (cp) genomes for both D. spathacea and D. cauda-felina. Comparative analysis revealed apparently different size and scaffold number between the two mt genomes, but a high similarity between the cp genomes.Eight regions with high sequence divergence were identified between the two cp genomes, which might be used for developing candidate DNA markers for distinguishing the two species. The splitting between D. spathacea and D. cauda-felina was inferred to occur at ~6.8 -7.7 million years ago (Mya), which may be driven by the environment fluctuations in late Miocene. In the cp genome, 12 genes related to the expression of photosynthesis-associated proteins were detected with signatures of positive selection, which may contribute to the origin and evolutionary adaptation of Dolichandrone mangrove species. These new findings do not only enrich organelle genomic resources of Dolichandrone species, but also provide important genetic clues for improving the conservation and proper usage of endangered mangrove associate D. spathacea.